Whole School Approach in Contribution Building Mental Health in Schools - Agustina, Yanuar Putri; Widodo, Prasetyo Budi (Universitas Islam Negeri Raden Intan Lampung, 2024)
Mental health is essential for everyone, including those in the realm of education. However, there are still many cases related to mental health that arise in schools. This is a special concern so that school mental health can be upheld. The purpose of this article is to find out the picture of mental health in schools and determine what efforts and roles teachers play in building mental health in schools. The literature study method was done by summarizing, analyzing, and synthesizing several relevant literatures. The analysis results show that internal and external factors influence mental health. Mental health problems in Indonesian school environments are generally caused by low literacy rates related to the issue. In this case, teachers have a strategic role not only as information providers but also as role models who can positively influence the psychosocial development of students. Building mental health in schools can be done through mental health promotion efforts where all components of the school, including the organization within it and parents of students, contribute to support the development of mental health in schools. Keywords: literature review, mental health, teacher role, whole school approach